Boswell's enlightenment - Zaretsky, Robert (Cambridge, Massachusetts : The Belknap Press of Harvard University Press, 2015)
"In 1763, the young James Boswell left Great Britain for a 'Grand Tour' of the Continent. The tour was a tradition among British and Scottish youths; by visiting the great historical sites, especially those of Roman and Greek antiquity, they would complete the studies they had begun at universities back home. Boswell's tour, however, was different: he was less concerned with the ruins of the past than the thinkers of the present. In particular, he was eager to question the leading figures of the Enlightenment on matters of faith and God--of particular importance to Boswell, who had been raised in the dour and dire atmosphere of the Church of Scotland. In his remarkable conversations with figures like Voltaire, Rousseau, and Hume, we see a man struggling with the claims of reason and needs of faith--a struggle that remains very much our own 250 years later"--Provided by publisher.
Prologue : the view from Arthur's Seat -- In the Kirk's shadow -- At home with Hume -- A journal is born -- Enter Johnson -- Derelict in Utrecht -- Belle de Zuylen -- Aufklarüng Agonistes -- The distance between Môtiers and Ferney -- On libertines and liberty -- After Corsica, before futurity.
Includes bibliographical references and index.
Keywords: Boswell, James. -- Travel -- Europe; Authors, Scottish -- 18th century -- Biography; Enlightenment -- Scotland; Philosophy and religion -- Scotland -- History -- 18th century; Scots -- Europe -- History -- 18th century; Travelers -- Europe -- History -- 18th century; Europe -- Description and travel; elämäkerrat